Peculiarities of sediments of slightly magnetized admixtures on spherical ferromagnetic adapter - Горобец C. B. (Proceedings of National Aviation University, 2000)
Considered is theoretical substantiation of magnetic susceptibility of slightly magnetized microobjects depending on their angle of fallout on spherical ferromagnetic adapter placed into external permanent homogeneous magnetic field. It is shown that by solving the equation of slightly magnetized admixture motion in the proximity of the spherical ferromagnetic adapter it is possible to receive the value of magnetic susceptibility of a microobject at a definite (determined experimentally) angle of sediment on the nozzle